Mental symptoms in post-COVID syndrome and post-COVID-19 vaccination syndrome: results of a representative population survey - Czaplicki, Andreas; Hipper, Leonie; Hegerl, Ulrich (Frontiers in Public Health, 2025)
BackgroundMental symptoms such as fatigue, concentration difficulties, and sleep disorders are frequently reported in both Post-COVID Syndrome (PCS) and Post-COVID-19 Vaccination Syndrome (PCVS). Although symptom profiles may overlap, comparative epidemiological data from the general population are limited.MethodsWe conducted a representative online survey of 4,632 adults in Germany and investigated mental symptoms associated with PCS and PCVS, including fatigue, cognitive problems, sleep disturbances, impaired performance and depressed mood. Socio-demographic factors, vaccination status, vaccine type and number of vaccinations were analysed.ResultsThe prevalence of self-reported mental symptoms of PCS was 12.1% among respondents, with women and younger individuals more commonly affected. The prevalence of self-reported PCVS was 12.6% among vaccinated individuals, with no significant gender differences, but fewer cognitive symptoms in older adults. Respondents with only one vaccination reported the highest rate of PCVS symptoms (20.8%), which decreased to 8.9% for those with four or more vaccinations. Differences between vaccine types were small overall, but non-mRNA vaccines were associated with a slightly higher rate of sleep and concentration problems.ConclusionMental symptoms are relatively common after both SARS-CoV-2 infection and vaccination and show overlap, especially fatigue. These findings highlight how difficult it is to distinguish PCS from PCVS and emphasize the need to consider alternative explanations, such as undiagnosed depressive disorders, in clinical assessments.